AN EPIDEMIOLOGICAL APPROACH TOWARD THE DRUG ADDICTION IN TEHRAN - D.Shojaizadeh; M. Rabiian (Tehran University of Medical Sciences, 1997)
This study took an epidemiological approach toward the problem of drug addiction in Tehran. The subjects were 300 addicts chosen on the basis of stratified random selection out of the population of 3627 prisoners who were all proven addicts and sentenced to imprisonment by the court in the year 1370. A descriptive survey showed that drug addiction generally, and heroin addiction specifically, is more common among the youth. In fact, 89.7% of the addicts were between 15 and 40 years old, with the average age of 32.5% years. The data are summarized in 6 tables and statistical computations, especially the chi-square test which was applied to determine correlation coefficients between the sets of dependent and independent variables, showed that the following factors have the highest influence on this growing phenomenon: Availability of drugs; lack of hobbies; lacking clear objectives and planning in one's life; socto-cultural pressure; family conflicts; illiterate parents; unemployment and immature character. The educational system should also be criticized as 35% of the sample had obtained their high school diploma. This suggests that should be a more effective syllabus for health education on junior high school curriculum and get the teenagers acquainted with the effects of drug addiction on one's health and its consequences.